Koli women sorting the fish for drying - Mumbai Archive Project Team (Jio Institute, 2024)
Koli women get together to prepare, dry, sort, and package the fish at a designated location close to the coast. Open areas with plenty of sea breeze and sunlight are ideal for drying.